Editorial Perspective: Maximising the benefits of intervention research for children and young people with developmental language disorder (DLD) – a call for international consensus on standards of reporting in intervention studies for children with and at risk for DLD. (20th September 2022) - Frizelle, Pauline; McKean, Cristina; Eadie, Patricia; Ebbels, Susan; Fricke, Silke; Justice, Laura M.; Kunnari, Sari; Leitão, Suze; Morgan, Angela T.; Munro, Natalie; Murphy, Carol‐Anne; Storkel, Holly L.; et al.
Abstract : Current methods for reporting interventions do not allow key questions of importance to practitioners, service providers, policy‐makers and people with DLD to be answered, and hence limit the implementation of effective interventions in the real world. To extend the existing EQUATOR guidelines to the context of speech language therapy/pathology for children with language disorder and to provide more specific guidance on participants, interventions and outcomes within the CONSORT checklist (used to improve the reporting of randomised controlled trials) and TIDieR (Template for Intervention Description and Replication) to ensure consistency of reporting. We will develop a core team to include representatives from each of the key groups who will either use or be influenced by the final reporting guidance across different countries. To achieve each set of aims, we will conduct reviews of the literature (which present typologies of intervention characteristics in (D)LD and related disorders); carry out focus groups; and use systematic consensus methods such as the Delphi technique, nominal group technique or consensus development conferences. Through the development and adoption of standard intervention reporting criteria, we anticipate that we will overcome the numerous barriers for practitioners, services and policy‐makers in applying intervention evidence to practice. We believe that establishing international consensus on reporting guidelines would significantly accelerate progress in DLD research and the ease with which it can be used in clinical practice, by capitalising on the growth in intervention studies to enable international collaboration and new methodologies of data pooling, meta‐analyses and cross‐study comparisons.